Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan Pada Jasa Laundry KW Ciputat - Masroni Masroni (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the effect of service quality and promotion on customer satisfaction at Laundry KW Ciputat. This type of research is quantitative with an explanatory approach. The population in this study were 1,877 Laundry KW Ciputat customers in 2023, with a sample size of 95 respondents determined using the Slovin formula. Data analysis used was simple linear regression analysis and multiple regression analysis using SPSS version 27. The results of this study indicate that, based on the results of the simple linear regression test, service quality has a positive and significant effect on strong customer satisfaction